2018
DOI: 10.1371/journal.pone.0195739
|View full text |Cite
|
Sign up to set email alerts
|

Can a single pulse transcranial magnetic stimulation targeted to the motor cortex interrupt pain processing?

Abstract: The modulatory role of the primary motor cortex (M1), reflected by an inhibitory effect of M1-stimulation on clinical pain, motivated us to deepen our understanding of M1’s role in pain modulation. We used Transcranial Magnetic Stimulation (TMS)-induced virtual lesion (VL) to interrupt with M1 activity during noxious heat pain. We hypothesized that TMS-VL will effect experimental pain ratings. Three VL protocols were applied consisting of single-pulse TMS to transiently interfere with right M1 activity: (1) VL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 70 publications
(86 reference statements)
1
19
0
Order By: Relevance
“…The number of subjects per group ranged from 4 to 30 subjects (a mean of 11.6 ± 5.7). However, only one study 35 performed a power analysis calculation to justify the number of subjects they used in their study. Despite the study cohort including a mean of 50.1% males, the majority of the studies had a sex imbalance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of subjects per group ranged from 4 to 30 subjects (a mean of 11.6 ± 5.7). However, only one study 35 performed a power analysis calculation to justify the number of subjects they used in their study. Despite the study cohort including a mean of 50.1% males, the majority of the studies had a sex imbalance.…”
Section: Resultsmentioning
confidence: 99%
“…In 10 of the within-group design studies, 5,10,16,24,31,41,61,67,68,73 the VL interventions to different brain sites, including sham, were conducted in separate sessions on different days. Moreover, in 12 5,10,16,24,31,35,42,50,61,67,68,73 of the within-subject design studies, the order of the stimulated areas was randomized or counterbalanced among participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference in results could be because the threshold of modulation in pain perception might be higher than that in motor behavior. Indeed, the virtual lesion technique using single TMS with the intensity of 120% motor threshold for the M1 affects motor behavior but not pain perception . Therefore, the intensity of tSMS might not be sufficient to modulate pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…Tsubokawa et al [35] have shown that chronic epidural stimulation of M1 can be very useful for controlling deafferentation pain secondary to thalamic lesions. The hyperactivity of nociceptive neurons in this kind of central pain is thought to be suppressed by the stimulation of the motor cortex, which not only inhibits burst firing in the vicinity of the damaged thalamus, but also induces neuroplastic effects on the thalamus itself [36].…”
Section: Understanding the Neural Effects Of Tdcs Combined With Aerobmentioning
confidence: 99%